Learning from history in British overseas security: case studies from intervention in the Middle East - Kettle, Louise (2015)
Recent problematic military interventions, as part of the Global War on Terror, have led to widespread criticism that British policy-makers have failed to learn lessons from history. At the same time as the accusations of not learning, the British government has repeatedly claimed that lessons have been learned, particularly from the disastrous war in Iraq. This thesis investigates these contradicting claims by analysing learning from the past in the Foreign and Commonwealth Office, Ministry of Defence and the Intelligence Community across four case studies of British military intervention in the Middle East; 1958 in Jordan, 1961 in Kuwait, the 1990-1991 Gulf War and 2003-2009 Iraq War. It provides a fresh analysis of these highly significant events, using previously undisclosed documents, offers an assessment of learning processes and concludes by recommending practical suggestions for the improvement of learning from history in the future.